Research on an Inference Algorithm for a Series of Three-Port Converter Topologies - Liu, Qianshi; Du, Qianqian; Li, Haijin; Zhu, Liying; Liu, Zhigang; Zhang, Xiaofeng; Xu, Guoning (IEEE transactions on circuits and systems. I, Regular papers, 2025)
With the development of sustainable energy industry, aerospace, power electronics technology, and electric vehicles, the demand for energy has become more urgent for humanity. A three port converter (TPC) that can combine photovoltaic cells with batteries has become a better solution at present. However, it is difficult to obtain an ideal TPC. Current TPCs typically have large weight, low efficiency and their topology has a lot of optimization space. This article proposes a topologies inference algorithm for TPC which describes the implementation process of various methods in detail. Different TPC topologies are obtained and experimentally verified. By comparing the different deduction methods proposed, a prototype was developed through branch combination multiplexing. The TPC uses gallium nitride (GaN) high electron mobility transistors (HEMTs) to operate at a frequency of 200 kHz. The power density of it reaches 5.291 W/cm3 and achieving a 92.8% efficiency with semi-regulated bus architecture.